1999
DOI: 10.1007/s005860050201
|View full text |Cite
|
Sign up to set email alerts
|

Non-specific low back pain in children and adolescents: risk factors

Abstract: IntroductionBackache in children and adolescents has traditionally been considered a rare and serious condition, causing one to suspect an organic, infectious, inflammatory or neoplastic origin. Several surveys, however, have revealed a high prevalence of backache, and particularly of lumbar pain, in these age groups, indeed sometimes similar to that reported for adults. The purpose of this article is to review the recent literature, published since 1992 [6], on this topic. Epidemiological dataThe prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
297
8
43

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 343 publications
(380 citation statements)
references
References 62 publications
(169 reference statements)
32
297
8
43
Order By: Relevance
“…These results were probably Independent variables entered together, discriminant coefficients C0.50 in italics Eur Spine J (2013) 22:1979-1985 1983 not affected by age-related side effects, although significance failed by 1.6 % for the comparison of controls and younger patients in a univariate analysis (Table 5). This result was in line with findings that revealed frontal plane asymmetries as risk factor for the development of low back pain [1,2]. In terms of our rasterstereography spinal form assessment, sagittal plane spine shape parameters could not be exposed clearly by multivariate factor analysis procedures as LBP indicating variables, but in discriminant analyses sagittal plane parameters were extracted as variables being able to separate controls from LBP patients of different age (Table 4).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These results were probably Independent variables entered together, discriminant coefficients C0.50 in italics Eur Spine J (2013) 22:1979-1985 1983 not affected by age-related side effects, although significance failed by 1.6 % for the comparison of controls and younger patients in a univariate analysis (Table 5). This result was in line with findings that revealed frontal plane asymmetries as risk factor for the development of low back pain [1,2]. In terms of our rasterstereography spinal form assessment, sagittal plane spine shape parameters could not be exposed clearly by multivariate factor analysis procedures as LBP indicating variables, but in discriminant analyses sagittal plane parameters were extracted as variables being able to separate controls from LBP patients of different age (Table 4).…”
Section: Discussionsupporting
confidence: 87%
“…Using video rasterstereography and multivariate analysis procedures, we found low back pain-associated spine shape parameters in the frontal plane, which was consistent with findings considering frontal plane asymmetries to be risk factors for the development of low back pain [1,2]. Parameters of the sagittal plane were extracted as being associated with low back pain, too.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These study findings may be important since a review on risk factors related to back pain at young age indicated that sitting is the most common factor associated with back pain reports in youngsters [1]. Furthermore, at adolescent age youngsters typically adopt stooping postures, which may result in pressure on the anterior aspects of the vertebral growth plates [32].…”
Section: Discussionmentioning
confidence: 79%
“…During this transition period, stooping postures are frequently adopted for whatever reason (feelings of shame for the changing body or imitations in conscious of being ''cool''), which may result in pressure on the anterior aspects of the vertebral growth plates [32]. As a final aspect, the mounting back pain reporting around the growth spurt [1] justifies research on the stability of early intervention effects in youngsters at secondary school age.…”
Section: Introductionmentioning
confidence: 99%